2021
DOI: 10.3390/ijms22136907
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Mechanism of Action of the Attributed Immunomodulatory Role of Eltrombopag in Primary Immune Thrombocytopenia: An In Silico Approach

Abstract: Eltrombopag is a thrombopoietin receptor (MPL) agonist approved for the treatment of primary immune thrombocytopenia (ITP). Recent evidence shows that some patients may sustain platelet counts following eltrombopag discontinuation. The systemic immunomodulatory response that resolves ITP in some patients could result from an increase in platelet mass, caused either by the direct action of eltrombopag on megakaryocytes through MPL stimulation, or potential MPL-independent actions on other cell types. To uncover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 100 publications
0
12
0
Order By: Relevance
“…We also concluded that the only independent factor for OR and CR was the number of MKs in the BM before the avatrombopag initiation, which was consistent with earlier studies on eltrombopag. 14,1620 In vitro studies revealed that eltrombopag acted in multiple ways including immune regulation, 27 ferric chelation, 28 and rescue for the function of hematopoietic stem cells impaired by interferon-gamma in the inflammatory micro-environment. 29 Nonetheless, the basic pharmacological mechanism of TPO-RAs was mainly through a combination of TPO receptor c-MPL, leading to the activation of JAK-STAT, PI3K, and ERK pathways that regulated megakaryocytopoiesis.…”
Section: Discussionmentioning
confidence: 99%
“…We also concluded that the only independent factor for OR and CR was the number of MKs in the BM before the avatrombopag initiation, which was consistent with earlier studies on eltrombopag. 14,1620 In vitro studies revealed that eltrombopag acted in multiple ways including immune regulation, 27 ferric chelation, 28 and rescue for the function of hematopoietic stem cells impaired by interferon-gamma in the inflammatory micro-environment. 29 Nonetheless, the basic pharmacological mechanism of TPO-RAs was mainly through a combination of TPO receptor c-MPL, leading to the activation of JAK-STAT, PI3K, and ERK pathways that regulated megakaryocytopoiesis.…”
Section: Discussionmentioning
confidence: 99%
“…TPO is usually produced by the liver, which regulates hematopoietic and megakaryocyte growth by binding to its receptor c-Mpl and triggering activation of the Janus kinase 2 (JAK2) / signal transducer and activator of transcription (STAT) pathway [3,4] . Many preclinical studies have con rmed the bene cial effect of TPO on the activation and maintenance of hematopoietic stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…The consistency of all these data is even more accentuated considering that RNA sequencing of blood cells subsets has revealed that TPO is expressed in immune cell subpopulations: T-regs, B lymphocytes, CD4 + and CD8 + T cells, monocytes, neutrophils, and NK cells ( Schmiedel et al, 2018 ; Monaco et al, 2019 ). Recently, an “in silico” approach has shown different pathways (upregulation of FOXP3 and PPARγ, attenuation of IFN-γ signaling) by which ELT may restore immune tolerance and reduce inflammation in the context of ITP ( Lozano et al, 2021 ). Interestingly, this model hypothesizes a potential pro-apoptotic BCL-2 mediated effect upon long term treatment with ELT, affecting the survival of platelets ( Lozano et al, 2021 ).…”
Section: Itp: Drawing the Perfect Picturementioning
confidence: 99%
“…Recently, an “in silico” approach has shown different pathways (upregulation of FOXP3 and PPARγ, attenuation of IFN-γ signaling) by which ELT may restore immune tolerance and reduce inflammation in the context of ITP ( Lozano et al, 2021 ). Interestingly, this model hypothesizes a potential pro-apoptotic BCL-2 mediated effect upon long term treatment with ELT, affecting the survival of platelets ( Lozano et al, 2021 ). On the other hand, experimental data show that ELT could directly inhibit the pro-apoptotic factor Bax, thus contributing to the fine regulation of cell survival pathways ( Spitz et al, 2021 ).…”
Section: Itp: Drawing the Perfect Picturementioning
confidence: 99%